Applications of Machine Learning in Networking: A Survey of Current Issues and Future Challenges - Ridwan M.A.; Radzi N.A.M.; Abdullah F.; Jalil Y.E. (Institute of Electrical and Electronics Engineers Inc., 2023)
Intrusion detection; Machine learning; Quality of service; Complex problems; Computational model; Future challenges; Improve performance; Ml algorithms; Performance issues; Resource management; Rule based algorithms; Complex networks